Interactive effects of external knowledge sources and internal resources on the innovation capability of Chinese manufacturers. Issue 8 (12th September 2016) - Wang, Zhiqiang; Wang, Qiang; Zhao, Xiande; Lyles, Marjorie A.; Zhu, Guilong
Abstract : Purpose: Chinese firms were operating within a closed economic environment before the "opening up" in the late 1970s, but it has only been in the late 1990s that China has recognized the importance of innovation. The Chinese government has attempted to rectify this liability by providing funding to assist Chinese firms in developing innovation capability by increasing R&D collaborations and employing external experts. The purpose of this paper is to study the innovation of Chinese firms by examining how internal and external resources interactively impact the innovation capability. Design/methodology/approach: Panel data collected from Chinese manufacturers are used to test the hypothesized relationships. Findings: The results have shown that the interplay between internal and external resources exhibits differential patterns of impact on innovation capability. The authors discover different moderating patterns of the two types of external resources: visiting experts are helpful in enhancing the effects of internal human resources, while R&D collaborations are useful in exploiting internal financial and physical resources, even when the main effect of financial resources on innovation capability is not significant. Originality/value: The study contributes to the literature by providing empirical evidences on the roles of absorbed external resources and knowledge to catalyze internal resources in building up innovation capability in an emerging economy.